NLMS Based Adaptive Control of Stable Plants - Shafiq, Muhammad (2020)
In this paper we propose a new stable adaptive controller for stable plants, which may be non-minimum phase. The controller is composed of adaptive finite impulse response (FIR) filter in the feedback loop. This adaptive FIR filter is designed online as an L-delay approximate inverse system of the given stable plant. The solution of Diophantine equation is not involved in the design procedure. Hence the numerical problems associated with the solution of Diophantine equation are avoided. Computer simulation results and real time experimental results are included in the paper to demonstrate the effectiveness of the proposed method.